2018
DOI: 10.1080/24750158.2018.1531678
|View full text |Cite
|
Sign up to set email alerts
|

Do University Libraries in Australia Actively Plan to Protect Special Collections from Disaster?

Abstract: Do university libraries in Australia actively plan to protect special collections from disaster? Abstract Despite the increasing digitalisation of special collections, Australian university libraries continue to house tangible original works contributing to collective state, national and global heritage. The protection of special collections relates to the international aspirations provided by the Sendai Framework for Disaster Risk Reduction 2015-2030 Priority 3 (United Nations, 2015). Currently over five hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In addition, our findings parallel those of Superio, Alayon and Oliveros (2019) and Superio, Abaday, Oliveros et al (2019), who studied academic libraries in Western Visayas and Marawi City, respectively, and Garnett et al (2018), who examined academic libraries in Australia. Across these studies, limited financial resources were identified as the primary reason for the absence of DMPs in libraries.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, our findings parallel those of Superio, Alayon and Oliveros (2019) and Superio, Abaday, Oliveros et al (2019), who studied academic libraries in Western Visayas and Marawi City, respectively, and Garnett et al (2018), who examined academic libraries in Australia. Across these studies, limited financial resources were identified as the primary reason for the absence of DMPs in libraries.…”
Section: Discussionsupporting
confidence: 85%
“…While regular library planning prepares for disasters of a reasonable size (Brown, 2018;Garnett, Arbon, Howard, & Ingham, 2018), the processes and theory behind these approaches are limited to knowledge from previous disasters. Library associations and cultural associations collect resources to develop our capacity and knowledge to deal with disasters again within this framework (American Library Association, 2017;Australian Library andInformation Association, 2018, 2010;Blue Shield Australia, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, Goldman found that institutions had not created policies to protect digital materials and their properties (Goldman 2011). Garnett et al also found that university libraries' special collection protection against disasters is under-researched (Garnett et al 2018). In most cases, university libraries require IT support; special collections that are made available online must be treated carefully in order that the information presented is complete.…”
mentioning
confidence: 99%